Analisis Moving Average Convergence Divergence pada Investasi Saham Syariah saat New Era - Dr. A. Ifayani Haanurat; Arman Arman; Nur'aeni Nur'aeni (EKONOMI KEUANGAN DAN BISNIS, 2022)
Abstract. This research aims to find out the optimal rate of return on investment at Islamic stocks based on the MACD method during the New Era, with the population of Islamic stocks or companies that included in the Liquid 45 or LQ-45 stock index and also included in Jakarta Islamic Index or JII during October to December 2021, and sample selection using purposive sampling technique, as well as using secondary data obtained from daily data on JPFA stock prices which had the highest stock return values. The results of this research showed that the use of the MACD indicator produced accurate purchase and sell signals on JPFA shares, this indicated that JPFA shares provided buy signals on October 06, November 02 2021 and December 30, 2021. It was proven by the fact that the MACD value was greater than The Signal Line caused result in a Bullish or Uptrend (the stock price signaled a signal that increased, so it was recommended to buy) while the JPFA stock showed a sell signal on October 05, 2021, November 01, 2021, and December 30, 2021 and it was proven by the fact that the MACD value was smaller than Signal Line then there was a Bearish or Downtrend (the stock price gave a signal to go down, it was recommended to sell). So, with the results of this study, technical analysis using the MACD indicator can be recommended to short-term investors to be used in making decisions to buy or sell shares during the New Era.